Infiltrating macrophages and interferon gamma rather than renal genotype dictate heightened crescentic glomerulonephritis - Du, Yong; Fu, Yuyang; Gao, Yuyang; Poojitha, Dugyala; Kamala, Vanarsa; Li, Quanzhen; Zhou, Xinjing; Mohan, Chandra (Frontiers in Immunology, 2024)
BackgroundBoth intrinsic renal cells and immune cells contribute to driving renal inflammation and damage. However, the respective roles of intrinsic renal cells and immune cells in crescentic glomerulonephritis, and the key molecular factors driving pathogenesis are still unclear.MethodsThe roles of intrinsic renal cells and renal infiltrating immune cells in crescent formation were explored using renal transplantation after experimental anti-GBM disease induction in 129x1/svJ and C57BL/6J mice. Both strains share MHC, but vary in anti-GBM nephritis susceptibility. The role of macrophage and IFN-γ in crescent formation was investigated using adoptive transfer of macrophages with altered IFN-γ expression. The gene expression profile difference between 129x1/svJ and C57BL/6J macrophages was compared using Affymetrix arrays and Gene Ontology (GO) enrichment analysis.ResultsB6 recipient mice transplanted with 129x1/svJ kidneys were resistant to anti-GBM challenge, as evidenced by stable renal function and less severe renal pathology. Conversely, 129x1/svJ recipient mice receiving B6 kidneys developed severe renal damage with crescent formation, comparable to the disease in parental 129x1/svJ mice. 129x1/svJ macrophages exhibited heightened IFN-γ and IFN-γ related gene expression compared to B6 macrophages. Adoptive transfer of 129x1/svJ macrophages with subdued IFN-γ expression reduced anti-GBM nephritis, while B6 macrophages with up-regulated IFN- γ expression worsened renal damage.ConclusionUsing renal transplantation between 129x1/svJ and C57BL/6J mice and anti-GBM disease induction, we found infiltrating immune cells, not intrinsic renal cells, to play the dominant role in initialing and driving glomerular crescent formation. In particular, macrophage IFN-γ expression was critical for crescent formation.